Increasing numbers of ship strikes in the Canary Islands: proposals for immediate action to reduce risk of vessel-whale collisions - Carrillo , Manuel; Ritter , Fabian (J. Cetacean Res. Manage., 2023)
The Canary Islands, known for their extraordinarily high cetacean species diversity, have witnessed a rapid expansion in fast and high speed ferry traffic during the past few years. At the same time, ship strikes have been increasingly reported. 556 cetacean carcasses, found ashore, or reported, in the Canary Islands between 1991 and 2007, were examined. 59 strandings (10.6%) were found to involve vessel-whale collisions, the great majority of strandings (58%) occurred on Tenerife. Species most affected were sperm whales (Physeter macrocephalus, n = 24, 41%), pygmy sperm whales (Kogia breviceps, n = 10, 17%), Cuvier’s beaked whales (Ziphius cavirostris, n = 7, 12%), short-finned pilot whales (Globicephala macrorhynchus, n = 6, 10%) and at least three baleen whale species (n = 9, 15%). Twenty six animals (44%, n = 42) were either calves or juveniles, and one was a newborn. The temporal distribution of strandings indicates that lethal strikes have increased in recent years. Most ship strikes, assumingly by large and fast moving vessels, probably resulted in the death of the animals, as indicated by severe injuries such as huge slashes, cuts, broken vertebrae or animals separated into halves. Given these numbers and the widely accepted fact that only a portion of ship strikes will be recorded due to under-reporting and carcasses drifting away or sinking, ship strikes appear to be a major threat to cetaceans in the Canary Islands, especially to sperm whales. Moreover, the issue is a matter of human safety, as crew and passengers are at risk of being harmed, too. In this situation, a number of measures to mitigate the risk of ship strikes are recommended as a matter of high priority. These include the placement of dedicated look-outs on fast moving vessels, the shift of ferry transects where feasible, a speed limitation for local high-risk areas where cetacean abundance is notably high, the introduction of an obligatory reporting system of vessel-whale collisions and the conduction of detailed studies dealing with this pressing issue.